Long-Term Results of Universal 2 Total Wrist Arthroplasty - Zijlker, H. J. A.; Ritt, M. J. P. F.; IJsselstein, C. B. (Journal of Wrist Surgery, 2019)
Background The Universal 2 is a widely used total wrist implant that aims to maintain function of the wrist.Purpose Promising mid-term results of the Universal 2 total wrist implant are described in the literature. This study evaluates the long-term results in terms of implant survival and patient satisfaction.Patients and Methods Patients who received a Universal 2 implant between 2004 and 2009 were retrospectively identified through a database search. Clinical outcome and complications of the implant were assessed by examination of the patient's medical records, X-rays, and a questionnaire, consisting of the Patient-Rated Wrist and Hand Evaluation questionnaire (PRWHE) and Quick Disabilities of the Arm, Shoulder and Hand (QuickDASH) questionnaires and additional questions.Results Twenty-five patients (26 wrists) were included in this study. Twenty-one (81%) Universal 2 implants remained in situ after a mean follow-up of 11 years. Moderate PRWHE (44) and QuickDASH (41) scores were found in these cases. Five Universal 2 implants failed and were converted to a total wrist arthrodesis after a mean period of 9.2 years due to distal component loosening (n = 3), recurrent luxation (n = 1), or recurrent synovitis (n = 1). Twenty-three (92%) patients were (very) satisfied with the Universal 2 implant.Conclusion The Universal 2 demonstrates a high (81%) implant survival with a high patient satisfaction after a mean follow-up of 11 years. Prospective studies of the Universal 2 implant are necessary to objectify improvement in wrist function and to provide a better comparison to other fourth generation wrist implants.
Keywords: total wrist arthroplasty; wrist implant; Universal 2; long-term results